A donor-acceptor type electrochromic polymer and a preparation method thereof and a polymer film
Patent Information
- Application Number
- CN202211489433.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-11-25
AI Technical Summary
然而,吸收光谱能够覆盖近红外区域的聚合物报道较少,因此,开发具有可见光和近红外双吸收聚合物对电致变色领域有重要的意义
[0025] The donor-acceptor type electrochromic polymer and polymer film of the present invention have dual-band absorption properties of visible light and near-infrared, and can be used in electrochromic devices to obtain electrochromic devices with dual-band absorption of visible light and near-infrared. Polymer components.
Smart Images

Figure CN116023633B_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to the technical field of electrochromic change, and in particular to a donor-acceptor type electrochromic polymer and a preparation method thereof, and a polymer film. Background Art
[0002] Electrochromism is a phenomenon in which the color changes reversibly depending on the direction of the electric field when a voltage is applied. Since the first report, electrochromic materials have received extensive attention and become attractive synthetic materials. They have been widely used in the field of electrochromism, such as organic light-emitting diodes (OLEDs), anti-glare rearview mirrors, sunglasses, smart electrochromic windows, etc.
[0003] Generally, electrochromic materials include transition metal oxides, viologen small molecules, conductive polymers, etc. Among them, conductive polymers have become a hot spot in the current research and application of electrochromic materials due to their advantages such as designable structure, rich color changes, high contrast, fast response rate, high coloring efficiency and good stability. However, there are few reports on polymers whose absorption spectra can cover the near-infrared region. Therefore, the development of polymers with dual absorption of visible light and near-infrared is of great significance to the field of electrochromic materials.
[0004] There are still many technical challenges to be overcome as molecular systems for fine-tuning colors for non-emissive electrochromic devices such as smart windows, e-paper are developed. Over the years, the concept of "spectral engineering" (tailoring the complex interplay between molecular physics and various optical phenomena occurring in the electromagnetic spectrum) has become increasingly important in the field of π-conjugated organic polymers. In the spectral engineering toolbox, the "donor-acceptor" approach uses alternating electron-rich and electrorefractive moieties along the π-conjugated backbone. This approach is particularly valuable in the synthesis of dual-band and broadly absorbing chromophores with electrochromic properties.
[0005] In recent years, 4,9-dihydro-s-indolo[1,2-b:5,6-b0]dithiophene (IDT) has been increasingly used in organic optoelectronic devices. Due to the availability of sp3 hybridized carbon atoms on IDT, functional side chains can be easily attached to the IDT unit to increase its solubility in organic solvents. In addition, the inherent coplanar "ladder" structure of the IDT unit enhances the degree of π electron delocalization, making it highly electron-rich, so IDT is a typical electron donor unit.
[0006] Based on the structural characteristics of 4,9-dihydro-s-indolo[1,2-b:5,6-b0]dithiophene (IDT), receptor unit pairing design is carried out, and even its electrochromic properties are further regulated by introducing other structural units. This is of great significance for the development of various electrochromic polymers and the expansion of the electrochromic performance and application scope of IDT. Summary of the invention
[0007] The object of the present invention is to provide a donor-acceptor type electrochromic polymer, a preparation method thereof and a polymer film. The electrochromic polymer uses benzothiadiazole [3,4-g] quinoxaline (TQX) as an acceptor unit monomer and 4,9-dihydro-s-indolo [1,2-b:5,6-b0] dithiophene (IDT) as a donor unit monomer. The C=N double bond in the conjugated ring of the acceptor unit monomer can effectively enhance the electron-withdrawing ability while maintaining good planarity of the conjugated structure. The steric hindrance of TQX and donors such as thiophene is small, so that the absorption spectrum of the polymer can be located in the near-infrared region. The 4,7-dibromo-2,1,3-benzothiadiazole (TZ) unit monomer is used as a regulating unit monomer. Due to its electron-deficient characteristics, it is also a commonly used acceptor unit in the preparation of donor-acceptor type polymers. Its introduction is intended to regulate the near-infrared band of the polymer.
[0008] The technical solution of the present invention is to provide a donor-acceptor type electrochromic polymer, which includes one or two of the compounds shown in the following structural formula P1 and structural formula P2:
[0009]
[0010] In the structural formula P1 and the structural formula P2: R1 is a straight-chain alkyl group with more than 6 carbon atoms, R2 is a branched-chain alkyl group with more than 20 carbon atoms, and n represents the degree of polymerization, and the value of n is a natural number between 8 and 100.
[0011] The present invention also provides a method for preparing the donor-acceptor type electrochromic polymer, comprising the following steps:
[0012] 1) Preparation of polymer by Stille coupling: 4,9-dihydro-s-benzoindo[1,2-B:5,6-b']dithiophene M1, 4,7-dibromo-2,1,3-benzothiadiazole M2, benzothiadiazole[3,4-g]quinoxaline M3, xylene, tri(dibenzylideneacetone)dipalladium and tri(2-methylphenyl)phosphine are added as raw materials into a two-necked flask with an atmosphere protection and a condenser on top, and the mixture is vented to maintain the atmosphere protection in the flask, and the mixture is heated to react for a certain period of time and cooled to room temperature, and the reaction solution is dropped into methanol for precipitation, and the precipitate is collected by filtration;
[0013] 2) Purify the polymer by Soxhlet extraction: Wrap the above-mentioned precipitate with filter paper, place it in a fat extractor, wash it with methanol, n-hexane and chloroform in sequence, then concentrate the chloroform washing liquid, drop the concentrated liquid into methanol for precipitation, and filter and collect the precipitate to obtain the purified electrochromic polymer.
[0014] When the molar ratio of M1 to M3 in step 1 is 1:1 and the amount of M2 is zero, the electrochromic polymer obtained in step 2 is the compound represented by the above structural formula P1.
[0015] When the molar ratio of M1, M2 and benzothiadiazole [3,4-g] quinoxaline M3 is 2:1:1, the electrochromic polymer obtained in step 2 is the compound represented by the above structural formula P2.
[0016] The synthetic route of the present invention is as follows:
[0017]
[0018]
[0019] P2
[0020] R1 is a straight-chain alkyl group with more than 6 carbon atoms, R2 is a branched-chain alkyl group with more than 20 carbon atoms, and n represents the degree of polymerization, and the value of n is a natural number between 8 and 100.
[0021] Furthermore, in the above step 1), the molar ratio of 4,9-dihydro-s-indan[1,2-B:5,6-b']dithiophene to tri(dibenzylideneacetone)dipalladium is 1:(0.02-0.04); the molar ratio of 4,9-dihydro-s-indan[1,2-B:5,6-b']dithiophene to tri(2-methylphenyl)phosphine is 1:(0.1-0.2); and the amount of xylene used is such that the concentration of each monomer is 0.3 mol / L.
[0022] Furthermore, the reaction temperature in the above step 1) is 100-120° C., and the reaction time is 48-96 hours.
[0023] Furthermore, the purification process in the above step 2) is a Soxhlet extraction process, in which methanol, n-hexane and chloroform are used for extraction in sequence, and the chloroform solution is precipitated.
[0024] The present invention also provides a polymer film, which is obtained by spraying or scraping the donor-acceptor type electrochromic polymer provided by the present invention, and the film thickness of the polymer film is 300-800nm. The present invention is an electrochromic polymer with visible light and near-infrared dual-band absorption, which can be formed on the surface of a conductive substrate by scraping and spraying a solution, and its color is converted between a colored state and a transparent state, and has the characteristics of low driving voltage, high optical contrast, and high stability, and is suitable for assembly and application of electrochromic devices.
[0025] The donor-acceptor type electrochromic polymer and polymer film of the invention have visible light and near infrared dual-band absorption performance, can be applied to electrochromic devices, and obtain an electrochromic polymer component with visible light and near infrared dual-band absorption.
[0026] The advantages of the present invention compared with the prior art are:
[0027] The electrochromic polymer of the present application includes both acceptor units and donor units. The C=N double bond in the conjugated ring of the acceptor unit monomer can effectively enhance the electron-withdrawing ability while maintaining the good planarity of the conjugated structure, and the steric hindrance of the combination with the donor unit is small, so that the polymer absorption spectrum can be located in the near-infrared region, achieving the dual-band absorption performance of visible light and near-infrared. The present application also uses 4,7-dibromo-2,1,3-benzothiadiazole (TZ) unit monomer as a regulating unit monomer, which can further regulate the near-infrared band of the polymer on the basis of dual-band absorption. The preparation method of the present application is simple in process and can realize the mass preparation and production of electrochromic polymers. Using the principle of polymer spectral absorption, the donor-acceptor type electrochromic polymer structure design and preparation covering the visible light and near-infrared bands are realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] These and / or other aspects and advantages of the present invention will become more clear and easier to understand from the following detailed description of the embodiments of the present invention in conjunction with the accompanying drawings, in which:
[0029] Figure 1 This is the H-NMR spectrum of the polymer IDT-TQX obtained in Example 1 of the present invention;
[0030] Figure 2 This is the H NMR spectrum of the polymer IDT-TZ-TQX-2-1-1 obtained in Example 1 of the present invention;
[0031] Figure 3 The spectral absorption curves of the polymer obtained in Example 1 of the present invention dissolved in chloroform, wherein (a) is the spectral absorption curve and photo of the polymer IDT-TQX dissolved in chloroform; (b) is the spectral absorption curve and color photo of the polymer IDT-TZ-TQX-2-1-1 dissolved in chloroform;
[0032] Figure 4 The UV-visible absorption spectra and color change photos of the thin films formed by the polymer obtained in Example 1 of the present invention at different potentials, (a) is the thin film obtained by the polymer IDT-TQX; (b) is the thin film obtained by the polymer IDT-TZ-TQX-2-1-1;
[0033] Figure 5The transmittance comparison curves of the thin film formed by the polymer obtained in Example 1 of the present invention in the oxidized state and the reduced state, wherein (a) is the thin film obtained by the polymer IDT-TQX; (b) is the thin film obtained by the polymer IDT-TZ-TQX-2-1-1;
[0034] Figure 6 The cyclic voltammetry curves of the thin film formed by the polymer obtained in Example 1 of the present invention at different scanning rates, wherein (a) is a curve showing the current density of the thin film obtained by the polymer IDT-TQX as a function of voltage; (b) is a curve showing the current density of the thin film obtained by the polymer IDT-TQX as a function of scanning rate; (c) is a curve showing the current density of the thin film obtained by the polymer IDT-TZ-TQX-2-1-1 as a function of voltage; (d) is a curve showing the current density of the thin film obtained by the polymer IDT-TZ-TQX-2-1-1 as a function of scanning rate;
[0035] Figure 7 The transmittance response and stability curves of the thin film formed by the polymer obtained in Example 1 of the present invention are shown in Figure 1, wherein (a) is the transmittance response curve of the thin film obtained from the polymer IDT-TQX over time; (b) is the expansion of a section of the curve shown in Figure (a); (c) is the transmittance response curve of the thin film obtained from the polymer IDT-TZ-TQX-2-1-1 over time; and (d) is the expansion of a section of the curve shown in Figure (c). DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0037] Example 1
[0038] A method for preparing an electrochromic polymer having dual-band absorption of visible light and near infrared light comprises the following steps:
[0039] (1) Synthesis of benzothiadiazo[3,4-g]quinoxaline (TQX)
[0040] 4,7-dibromobenzo[C][1,2,5]thiadiazole-5,6-diamine (1 g, 3 mmol), product 1,2-bis(4-(decyloxy)phenyl)ethane-1,2-dione (1.5 g, 2.8 mmol) and 40 ml glacial acetic acid were added to a 100 ml round-bottom flask. The reaction mixture was refluxed overnight, cooled to room temperature, poured into 100 ml deionized water, extracted with dichloromethane, dried over anhydrous magnesium sulfate, and purified by column chromatography to obtain an orange-red solid. The yield was 80%; the corresponding nuclear magnetic resonance hydrogen spectrum 1H NMR (400MHz, CDCl3): 7.96-7.80 (d, 4H), 6.98-6.95 (d, 4H), 3.90 (d, 4H), 1.81 (sep,2H), 1.29 (m, 64H), 0.90 (m, 12H). Nuclear magnetic resonance carbon spectrum 13C NMR (101 MHz, CDCl3): δ 161.47 , 155.74 , 138.07, 132.64, 131.88, 71.14, 38.10, 31.93, 31.27, 30.04,26.88, 22.71, 14.30.
[0041] (2) Synthesis of electrochromic polymers
[0042] 1. 0.1mmol of 4,9-dihydro-s-benzoindano[1,2-B:5,6-b']dithiophene (IDT), 0.1mmol of benzothiadiazo[3,4-g]quinoxaline (TQX), 0.006mmol of tri(dibenzylideneacetone)dipalladium, and 0.03mmol of tri(2-methylphenyl)phosphine were placed in a 25mL two-necked bottle, ventilated and injected with nitrogen, and 15mL of anhydrous xylene was injected, and then ventilated and filled with nitrogen, heated to 120℃ and refluxed for 72h. After the reaction was completed, the reaction solution was cooled to room temperature, and the reaction solution was dripped into cold methanol for precipitation. The precipitate was filtered and dried; then Soxhlet extraction was performed with methanol, n-hexane and chloroform respectively, and the extraction time for each time was 24h. The chloroform extract was concentrated to 15mL, and then dripped into cold methanol to precipitate to obtain a black solid. The target polymer IDT-TQX was obtained by filtration and drying, and the yield was 68%.
[0043] 2. Place 0.2 mmol of 4,9-dihydro-s-benzoindano[1,2-B:5,6-b']dithiophene (IDT), 0.1 mmol of 4,7-dibromo-2,1,3-benzothiadiazole (TZ), 0.1 mmol of benzothiadiazole[3,4-g]quinoxaline (TQX), 0.006 mmol of tris(dibenzylideneacetone)dipalladium, and 0.03 mmol of tris(2-methylphenyl)phosphine in a 25 mL double-necked bottle. , ventilate and inject nitrogen, inject 15mL of anhydrous xylene, ventilate and fill with nitrogen, heat to 120℃ and reflux for reaction for 72h, cool to room temperature after the reaction, drop the reaction solution into cold methanol for precipitation, filter the precipitate and dry it; then perform Soxhlet extraction with methanol, n-hexane and chloroform respectively, each extraction time is 24h, concentrate the chloroform extract to 15mL, drop it into cold methanol to precipitate to obtain a black solid, filter and dry to obtain the target polymer IDT-TZ-TQX-2-1-1, and the yield is 72%.
[0044] The H NMR spectrum of the target polymer IDT-TQX is shown in Figure 1 ; The H NMR spectrum of the target polymer IDT-TZ-TQX-2-1-1 is shown in Figure 2 .
[0045] Example 2
[0046] The polymer prepared in Example 1 was subjected to solution spectrum and electrochemical performance tests. The polymer was dissolved in chloroform to prepare a solution with a concentration of 2*10-4 mg / mL. The solution absorption curve and the photo are shown in FIG. Figure 3 As shown, the polymer IDT-TQX solution is yellow, and the polymer IDT-TZ-TQX-2-1-1 solution is green. Through the test of UV-visible spectrophotometer, the solutions of the two polymers have visible light and near-infrared dual-band absorption, and show several high absorption peaks, which are the result of the combined action of π electron transition and intramolecular charge transfer. Among them, the absorption peaks corresponding to polymer IDT-TQX are at 369nm, 448nm and 887nm respectively. The absorption peaks corresponding to polymer IDT-TZ-TQX-2-1-1 are at 426nm, 629nm and 857nm respectively.
[0047] Preparation of polymer film: dissolve the polymer in chloroform to prepare a 4mg / ml solution, filter out the insoluble matter through a filter, place it in a spray gun, control the air pressure to 2MPa, spray it on the conductive glass, the film absorbance is about 1.0, and place it in a vacuum drying oven at 45 degrees for vacuum drying. A three-electrode system with a polymer film as the working electrode, a platinum wire as the counter electrode, and a calibrated silver wire as the reference electrode is used, and the supporting electrolyte is: 0.1mol / L lithium perchlorate propylene carbonate solution.
[0048] The copolymer film was tested for spectroelectrochemical performance under different voltages. A three-electrode system was used, with platinum wire as the counter electrode, calibrated silver wire as the reference electrode, polymer film as the working electrode, and the supporting electrolyte being 0.1 mol / L lithium perchlorate propylene carbonate solution. The spectroelectrochemical spectra and color-decolorized photos of the two copolymer films under different applied voltages are shown in Figure 4 , indicating that the copolymer films all have obvious electrochromic properties. Due to the accumulation of π-π* bonds, the spectrum of the polymer film has a certain red shift relative to the solution. As the voltage continues to increase, the polymer film can achieve a transition from a neutral state to a transparent state.
[0049] To investigate the optical contrast of polymer films in the visible and near-infrared regions, the transmittance of IDT-TQX and IDT-TZ-TQX-2-1-1 films in neutral and oxidized states was measured (see Figure 5 ). As can be seen from the figure, the contrast of IDT-TQX film in the visible region (600nm) is 48.2%, and the contrast in the near-infrared region (1210nm) is 87.1%. The contrast of IDT-TZ-TQX-2-1-1 film in the visible region (600nm) is 39.9%, and the contrast in the near-infrared region (1210nm) is 64.5%. This provides the possibility for the application of the two polymers in the visible and near-infrared bands.
[0050] The electrochemical properties of the copolymers were tested by cyclic voltammetry (see Figure 6 ), showing cyclic voltammetry curves at different scan rates. It can be found that the peak current density of the anode and cathode of the polymer gradually increases with the increase of the scan rate. Both polymers have low oxidation potentials. The initial oxidation potential of IDT-TQX is 0.46V, and the initial oxidation potential of IDT-TZ-TQX-2-1-1 is 0.5V. During the ion doping and anti-doping process, the peak current density and the scan rate are linearly related, indicating that the redox process of the membrane is unrestricted diffusion controlled and has good reversibility.
[0051] The cycling stability of the polymer was tested by using a UV-visible spectrophotometer and an electrochemical workstation (see Figure 7), the three-electrode system was connected to the electrochemical workstation, and the quartz cuvette was placed in the UV-visible spectrophotometer. While applying voltage to the polymer film, the transmittance change at the wavelength of maximum transmittance was measured simultaneously. The transmittance of IDTTQX at 1200nm did not show obvious attenuation after 200 cycles. The transmittance of IDT-TZ-TQX-2-1-1 at 1200nm still maintained a high contrast ratio of 69.1% after 500 cycles of switching. This shows that both polymers have a long cycle life.
[0052] It can be seen from the above embodiments that the color and absorption spectrum of the copolymer film prepared by the present invention can be regulated by the type of copolymer monomers, the copolymer film can achieve a transformation from colored to transparent, and has the characteristics of low driving potential, high coloring efficiency, good stability, etc. The prepared copolymer film can be used in the fields of electrochromic display, adaptive camouflage, etc.
[0053] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. Therefore, the scope of protection of the present invention should be subject to the scope of protection of the claims.
Claims
1. A method for preparing a donor-acceptor type electrochromic polymer, characterized in that: The following steps are involved: 1) Preparation of polymer by Stille coupling: M1, M3, 4,7-dibromo-2,1,3-benzothiadiazole (M2), xylene, tri(dibenzylideneacetone)dipalladium and tri(2-methylphenyl)phosphine are added into a two-necked flask with an atmosphere protection and a condenser on top, and the mixture is heated to react for a certain period of time and cooled to room temperature. The reaction solution is dropped into methanol for precipitation, and the precipitate is collected by filtration; The structural formula of the M1 is: The structural formula of the M3 is: ; 2) Purifying the polymer by Soxhlet extraction: Wrap the above precipitate with filter paper, place it in a fat extractor, wash it with methanol, n-hexane and chloroform in sequence, then concentrate the chloroform washing liquid, drop the concentrated liquid into methanol for precipitation, and filter and collect the precipitate, which is the purified electrochromic polymer; The structural formula of the donor-acceptor type electrochromic polymer is shown in P2: In the structural formula P2: R1 is a straight-chain alkyl group with more than 6 carbon atoms, R2 is a branched-chain alkyl group with more than 20 carbon atoms, and n represents the degree of polymerization, and the value of n is a natural number between 8 and 100.
2. The method for preparing a donor-acceptor type electrochromic polymer according to claim 1, characterized in that: The molar ratio of M1, M2 and M3 is 2:1:
1.
3. The method for preparing a donor-acceptor type electrochromic polymer according to claim 1, characterized in that: In the step 1): The molar ratio of M1 to tris(dibenzylideneacetone)dipalladium is 1:(0.02~0.04); The molar ratio of M1 to tri(2-methylphenyl)phosphine is 1:(0.1-0.2); The amount of xylene used was such that the concentration of each monomer was 0.3 mol / L.
4. The method for preparing a donor-acceptor type electrochromic polymer according to claim 1, characterized in that: The reaction temperature in step 1) is 100-120° C., and the reaction time is 48-96 hours.
5. The method for preparing a donor-acceptor type electrochromic polymer according to claim 1, characterized in that: The purification process in step 2) is a Soxhlet extraction process, in which methanol, n-hexane and chloroform are used for extraction in sequence, and the chloroform solution is precipitated.
6. A polymer film, characterized in that The polymer film is obtained by spraying or scraping the donor-acceptor type electrochromic polymer prepared by the preparation method according to claim 1, and the film thickness of the polymer film is 300-800 nm.
Citation Information
Patent Citations
Method for producing conjugated polymer, conjugated polymer, photoelectric conversion element, solar cell, and solar cell module
CN103917575A